Exploration of General Practice Education in Undergraduate Medical Education from the Perspective of Healthy China - YANG Shan, WANG Cong, WANG Liuyi (Zhongguo quanke yixue)
The outline of the "Healthy China 2030" Plan puts forward the idea of "sharing, co-construction and health for all". As the gatekeeper of residents' health, the training of general practitioners is crucial. Undergraduate education is the foundation of clinical education in medical colleges and the core of future medical talent reserves. Its teaching quality and effectiveness have a significant impact on the development and scale of clinical medicine in China. This article compares the situation of general practice education in undergraduate medical education at home and abroad, and finds that although Chinese universities currently offer general practice courses, the curriculum and content system are still not sound. Building a group of general medicine courses, strengthening medical humanities and ideological and political education in courses, innovating teaching methods, and improving teaching evaluation may be beneficial for promoting general medicine education in China and helping to promote the cause of national health.